The application of aqueous two-phase systems to oligosaccharide synthesis by alpha-mannosidase catalysed glycosyl transfer reactions. - Bartlett, T; Rastall, R; Rees, N; Adlard, M; Bucke, C (1992)
Aqueous two-phase systems formed from PEG and dextran have been applied to the synthesis of oligosaccharide by Jack bean alpha-mannosidase in reverse. Whilst rates of synthesis and percentage yields were similar in two-phase systems and one-phase aqueous buffer systems, a ten-fold increase in yield of product per unit of enzyme was seen. In addition, the use of aqueous two-phase systems offers potential process advantages over one-phase systems for the synthesis of oligosaccharides.